Dynamical systems method for solving nonlinear equations with monotone operators. - Hoang, N. S.; Ramm, Alexander G. (My University, 2009)
A version of the Dynamical Systems Method (DSM) for solving ill-posed nonlinear equations with monotone operators in a Hilbert space is studied in this paper. An a posteriori stopping rule, based on a discrepancy-type principle is proposed and justified mathematically. The results of two numerical experiments are presented. They show that the proposed version of DSM is numerically efficient. The numerical experiments consist of solving nonlinear integral equations.
Keywords: Dynamical systems method (DSM); Nonlinear operator equations; Monotone operators; Discrepancy principle